2012
DOI: 10.5152/balkanmedj.2011.036
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Apelin on Mesenteric Ischemia and Reperfusion Damage in an Experimental Rat Mode

Abstract: Objective: Intestinal ischemia-reperfusion (I/R) injury is associated with high morbidity and mortality rates. There is ongoing research to find an effective preventive or treatment agent. We aimed to evaluate the effects of apelin 13 (AP) on intestinal I/R injury in a rat model. Material and Methods:Twenty-four male Sprague-Dawley rats aged 6-8 weeks and weighing 280±20 g were equally divided into three groups (control, I/R and I/R+AP). The control group underwent superior mesenteric artery (SMA) mobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Moreover apelin behaves as CAT activator as documented previously by Foussal et al 44 Improvement of hepatic antioxidant, GSH, with decreased MDA, under apelin treatment has been recorded previously in vitro, 41 and in vivo, in mesenteric I/R induced hepatic injury. 45 Increased leukocyte infiltration in AP group compared to the control one observed in our study, is a multistep process, coordinated by specific adhesion molecules and a major characteristic of human and experimental pancreatitis, constituting a critical link in mediating tissue damage in AP. A fact is supported by reduced tissue injury in Cn-induced AP with neutrophils depletion.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover apelin behaves as CAT activator as documented previously by Foussal et al 44 Improvement of hepatic antioxidant, GSH, with decreased MDA, under apelin treatment has been recorded previously in vitro, 41 and in vivo, in mesenteric I/R induced hepatic injury. 45 Increased leukocyte infiltration in AP group compared to the control one observed in our study, is a multistep process, coordinated by specific adhesion molecules and a major characteristic of human and experimental pancreatitis, constituting a critical link in mediating tissue damage in AP. A fact is supported by reduced tissue injury in Cn-induced AP with neutrophils depletion.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, researchers have increasingly focussed on the effect of the apelin/APJ system on ischemia/reperfusion (I/R) injury (Chen, Wu, Li, & Chen, ; Y. Yang, Lv, Lyu, Wu, & Chen, ). The pathophysiology of I/R injury is extremely complex, including vascular endothelial cells, leukocytes, oxygen radicals, inflammatory mediators such as platelet‐activating factor and tumor necrosis factor, and adhesion molecules (Sagiroglu et al, ). Apelin could activate multiple protective mechanisms to prevent the heart, brain, liver, and kidney I/R injury (Y. Yang et al, ).…”
Section: The Role Of Apelin/apj System In Digestive System Diseasesmentioning
confidence: 99%
“…Irregular dilate arteries express higher levels of apelin. A signal for arteriogenesis in HCC(Muto et al, 2014) Treated with F13A Inhibit tumor growth, decrease arterioles I/R injury 24 male Sprague-Dawley rats I/R model MDA levels were significantly higher in the I/R group, MDA levels were lower in the I/ R+AP group(Sagiroglu et al, 2012) Note. AMPK: AMP-activated protein kinase; AS: acute stress; BMP2: bone morphogenetic protein-2; CD: Crohn's disease; CHeS: chronic heterotypic stress; CHS: chronic homotypic stress; CLD: chronic liver disease; CP: chronic pancreatitis; CRC: colorectal cancer; CRF: corticotropin-releasing factor; CRT: concurrent chemoradiotherapy; DSS: sodium dextran sulfate; EC: endothelial cell; ERK: extracellular signalregulated kinase; GI: gastrointestinal; GC: gastric cancer; HCC: hepatocellular carcinoma; HIF-1a: hypoxia inducible factor1a; HPC: hematopoietic progenitor cell ; HSC: hematopoietic stem cell ; hsCRP: high sensitive C-reactive protein; HVPG: hepatic venous pressure gradient; IEM: immunoelectron microscopy; IHC: immunohistochemistry; Il-10 -/-: Il-10 deficient; I/R: intestinal ischemia-reperfusion; JNK: c-Jun N-terminal kinase; J o2: an agonistic anti-Fas antibody (clone); LPS: lipopolysaccharide; LXR: liver X receptor; MAT: mesenteric adipose tissue; MAPK: mitogen-activated protein kinase; MDA: malondialdehyde ; MIP: macrophage inflammatory protein; MMP: matrix metalloproteinases; NAFLD: nonalcoholic fatty liver disease; PDL: pancreatic duct ligation; PDGFRβ: platelet-derived growth factor receptor β; PGE2: prostaglandin E2; PI3K: phosphatidylinositol-4,5bisphosphate 3 kinase; PPAR-α: peroxisome proliferator-activated receptor α; PTHrP: parathyroid hormone-related protein; s-apelin: serum apelin; SREBP-1c: sterol regulatory element-binding protein 1c; STAT3: signal transducer and activator of transcription 3; TIMP: tissue inhibitors of matrix metalloproteinase; TNF-α: tumor necrosis factorα; UC: ulcerative colitis; VEGF: vascular endothelial growth factor; WIRS: water-immersion and restraint stress; 4-HNE: the concentration of 4-hydroxynonenal.…”
mentioning
confidence: 99%
“…Despite the fact that studies on mesenteric ischemia reperfusion injury treatment have been performed with many agents in the literature, no study on the effect of sesamin on mesenteric ischemia reperfusion injury has been seen [2628]. In a study conducted by Torun et al ., it has been shown that TAS, TOS, and OSI values may not only be an indication of oxidative or antioxidative status but may also be used to evaluate treatment response [29, 30].…”
Section: Discussionmentioning
confidence: 99%